PAJAK EKSPOR, PERTUMBUHAN EKONOMI, DAN PENDAPATAN: KASUS AGROINDUSTRI DI INDONESIA - Lestari Agusalim (KINERJA, 2014)
This research aims to analyze whether export tax policy and the policy of productivity increment of agro industry based upstream and downstream sectors can increase real GDP growth, agro industry output, andhousehold income. The model used in this research is a comparative static Computable General Equilibrium (CGE) model. The data used are from the 2008 Input-Output Table, the 2008 System Accounting Matrix (SAM)Table, and other relevant suporting sources. The three simulations conducted in this research are: (1) export tax policy on agro industry’s upstream sector (SIM1), (2) export tax and productivity increment policies on agro industry’s upstream sector (SIM2), and (3) export tax and productivity increment policies on agro industry’s upstream and downstream sectors (SIM3). The three simulations will be adjusted to the government’s policies to suport agro industries’ downstream. SIM1 has negative effect on real GDP and only increases agro industry output in certain sectors only. SIM2 and SIM3 have positive effect on real GDP and increases agro industryoutput. All simulations increase non-agricultural household incomes, and decrease agricultural household incomes.Keywords: agroindustry, export tax, real GDP, household income